Improving convolutional neural networks performance for image classification using test time augmentation - Kandel, Ibrahem (2022)
Kandel, I., & Castelli, M. (2021). Improving convolutional neural networks performance for image classification using test time augmentation: a case study using MURA dataset. Health information science and systems, 9(1), 1-22. [33]. https://doi.org/10.1007/s13755-021-00163-7